Formation and management of safety culture in the railway industry: best practices and strategies (Transport systems and technologies, 2023)
This article examines the current issue of safety culture in the railway industry, in particular, the formation and development of a safety culture on the railways of Ukraine. In the article emphasizes the uniqueness of the European model of railway safety culture. The purpose of the study is to comprehensively study the principles, methods and effectiveness of the formation and management of the safety culture in the railway industry. Recommended strategies include leadership commitment, staff engagement, training, communications, security audits, and technology use. A comparative analysis between the EU and Ukraine's railway system points to structural and regulatory differences, emphasizing the need for Ukraine to adapt European practices in the field of safety. The article also offers a structured approach to incident analysis and implementation of security practices, as well as the application of the Plan-Do-Check-Act cycle for systemic security management. These approaches aim to improve safety practices and ensure efficient transportation systems.
Keywords: Safety Culture, Railway Industry, Risk Management, Employee Education, Awareness, Technology, Safety Improvement, Organizational Safety.